2018
DOI: 10.1111/bcpt.12949
|View full text |Cite
|
Sign up to set email alerts
|

β‐adrenergic Receptor Blocker ICI 118,551 Selectively Increases Intermediate‐Conductance Calcium‐Activated Potassium Channel (IKCa)‐Mediated Relaxations in Rat Main Mesenteric Artery

Abstract: Endothelial IK and/or SK channels play an important role in the control of vascular tone by participating in endothelium-dependent relaxation. Whether β-AR antagonists, mainly used in hypertension, affect endothelial K channel function is unknown. In this study, we examined the effect of the β2-AR antagonist and inverse agonist ICI 118,551 on the IK /SK channel activity by assessing functional relaxation responses to several agonists that stimulate these channels. Mesenteric arterial rings isolated from male S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Stringent proof of IA requires that the inverse effect of one ligand is blocked by a neutral antagonist; however, most studies in the field have assumed that a given compound shown once or more often to reduce the basal receptor output agonist consistently acts via IA, but this is not necessarily the case. For instance, ICI 118,551 has repeatedly been shown to be an inverse agonist at β 2 -AR (see below); however, its inhibitory effect in the rat endothelium was neither mimicked by other known inverse agonists (e.g., carvedilol or nadolol) nor blocked or reversed by antagonists (e.g., propranolol) or agonists (e.g., salbutamol) [ 60 ], indicating that it may have acted by β-AR-independent mechanisms in this model. While this may be the exception, IA as an explanation of an observed effect should not be assumed too easily.…”
Section: Methodological Aspects Of Studying Iamentioning
confidence: 99%
“…Stringent proof of IA requires that the inverse effect of one ligand is blocked by a neutral antagonist; however, most studies in the field have assumed that a given compound shown once or more often to reduce the basal receptor output agonist consistently acts via IA, but this is not necessarily the case. For instance, ICI 118,551 has repeatedly been shown to be an inverse agonist at β 2 -AR (see below); however, its inhibitory effect in the rat endothelium was neither mimicked by other known inverse agonists (e.g., carvedilol or nadolol) nor blocked or reversed by antagonists (e.g., propranolol) or agonists (e.g., salbutamol) [ 60 ], indicating that it may have acted by β-AR-independent mechanisms in this model. While this may be the exception, IA as an explanation of an observed effect should not be assumed too easily.…”
Section: Methodological Aspects Of Studying Iamentioning
confidence: 99%
“…Based on the clinical trials and in vivo assays done, systemic doses have been used without toxicity in humans (up to 20 mg/kg), rodents (0.5 or 1 mg/kg) or rhesus monkeys (0.1 μg/kg). ICI, nowadays, is mainly used as control of β-blockers's specificity in physiological processes such us control of heart and vascular tone and SNC and muscular signaling [37][38][39][40] . Finally, ICI has been also used in cancer research showing a role in cell proliferation and signalling regulation 41,42 .…”
mentioning
confidence: 99%
“…Asterisk (*) indicates a significantly inhibition of responses by L-NAME/ODQ. Δ indicates significant further inhibitions of responses by TRAM-34 (P < .05, two-way ANOVA with Sidak's post hoc comparison) (Ozkan & Uma, 2017). These effects were mediated through interaction with K Ca 3.1, which contributed to β 3 -adrenoceptor-mediated vasorelaxation in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…The effects of PKI further suggest that β 1/2 ‐adrenoceptors inhibit β 3 ‐adrenoceptors through a PKA‐mediated mechanism. β 1 ‐adrenoceptors were shown to inhibit ACh‐induced, endothelium‐dependent relaxation of the rat mesenteric artery through cAMP/PKA (Yarova et al, 2013), while ICI 118,551 enhanced aspects of endothelium‐dependent vasodilation in the same vessel type (Ozkan & Uma, 2017). These effects were mediated through interaction with K Ca 3.1, which contributed to β 3 ‐adrenoceptor‐mediated vasorelaxation in the present study.…”
Section: Discussionmentioning
confidence: 99%